Inter-Trans-Multi Disciplinary Model Approach of Integration of Knowledge and its Impacts on Academic and Career - Usman Syihab; Rusli Hasbi (TSAQAFAH, 2023)
This article discusses the inter-trans-multidisciplinary approach as a model of integration of knowledge and its impacts on academic horizon and career according to the perceptions of alumni with non-Islamic studies background of Postgraduate School of Syarif Hidayatullah Jakarta State Islamic University (SHJSIU). The research in this article used library research and field studies through interviews and questionnaires. The results showed that the curriculum of the Masters and Doctoral Studies program of Islamic Studies at Postgraduate School of SHJSIU is in accordance with the school mission of integration of knowledge, and that the inter-trans-multi-disciplinary approach has positive impacts on the development of academic horizons across disciplines and alumni career.